Lexis In Compositions Of ESL Students In A Selected University College In Nilai, Malaysia - Teoh, Lai Neo (2009)

(untitled)
This study aimed to address the gap in studies on lexical frequency profiles (LFP) of compositions among young adult ESL learners in a selected private university college in Nilai, Negeri Sembilan in Malaysia. The objectives of the study were to examine the quality of ESL writing in terms of the LFP, and to explore whether vocabulary learning strategies treatment would result in an improvement in vocabulary knowledge that would generate a rich lexical profile and subsequently quality in writing. In the study, two intact groups, formed the experimental and control groups. Each group comprised 31 participants enrolled in a writing course in the American Transfer Degree Programme in a selected private university college in Nilai, Negeri Sembilan. In the first phase of the study, for pre-post tests, both groups wrote a composition of between 300 and 450 words. A computer programme, VocabProfile categorized the vocabulary produced in the compositions into four levels of word frequency: first 1000-, second 1000-, Academic Word List, and not-in-the-list word levels, which determined the LFP of the compositions produced by the ESL learners. The compositions were also holistically scored for vocabulary. Second, the Vocabulary Levels Test and the Productive Levels Test were administered to the learners in the pre-test and post-test to determine the vocabulary size and depth. In addition to regular instruction as prescribed by the syllabus, the experimental group received treatment for eight weeks in the use of vocabulary learning strategies through vocabulary tasks, whilst the control group received regular instruction according to the prescribed syllabus. Data collected consisted of ESL compositions, LFP, vocabulary scores, journal writing reports, and a questionnaire data. The findings revealed that the vocabulary learning strategies frequently used by the ESL learners, in descending order, were cognitive, metacognitive, memory, compensation and social. The experimental group had improved significantly in their vocabulary size at the first 2000- and 10,000-word levels, and in their productive vocabulary (depth) at the 3000- and Academic Word List word levels. Data analysis showed that the LFP of the experimental group was at the first 2000-word level, and that there was a weak relationship between the holistic vocabulary scores and the LFP.